2006
DOI: 10.1111/j.1439-0396.2006.00621.x
|View full text |Cite
|
Sign up to set email alerts
|

Bee pollen product supplementation to horses in training seems to improve feed intake: a pilot study

Abstract: The objective of this study was to determine the efficacy of supplementation of Dynamic Trio 50/50, a bee pollen-based product, to improve physical fitness, blood leukocyte profiles, and nutritional variables in exercised horses. Ten Arabian horses underwent a standardised exercise test (SET), then were pair-matched by sex and fitness and randomly assigned to BP (receiving 118 g of Dynamic Trio 50/50 daily) or CO (receiving 73 g of a placebo) for a period of 42 days. A total collection was conducted from days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
(14 reference statements)
1
12
0
Order By: Relevance
“…A recent pilot study in horses demonstrated bee pollen supplementation on physical itness parameters, immunological status, and nutritional variables in Arabian horses in training. It was observed that supplementation with a commercial 55% bee pollen for 42 days did not change physical itness or immunological variables in the horses but it signiicantly increased feed consumption and nutrient retention in the same horses [54].…”
Section: Super Foods and Functional Food For Horsesmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent pilot study in horses demonstrated bee pollen supplementation on physical itness parameters, immunological status, and nutritional variables in Arabian horses in training. It was observed that supplementation with a commercial 55% bee pollen for 42 days did not change physical itness or immunological variables in the horses but it signiicantly increased feed consumption and nutrient retention in the same horses [54].…”
Section: Super Foods and Functional Food For Horsesmentioning
confidence: 95%
“…Bee is collected from lower pollen and is a natural food for horses, and can bring them into a healthy springtime bloom anytime of the year [53]. There are numerous reports of the beneits of supplemented bee pollen in horses including improved oxygen utilization, lower heart rates, and irmer muscle tone [54]. A recent pilot study in horses demonstrated bee pollen supplementation on physical itness parameters, immunological status, and nutritional variables in Arabian horses in training.…”
Section: Super Foods and Functional Food For Horsesmentioning
confidence: 99%
“…of Turner et al (2006) who detected, that phytoadditives such as anise or bee pollen can significantly increase feed intake and subsequently increased the nutrients retention. A blend of origanum, anise and citrus fruits essential oils were analyzed in saccharides digestibility point of view also.…”
Section: Tablementioning
confidence: 99%
“…Bee pollen is used widely as a dietary supplement in equine industry, with many trainers reporting anecdotally numerous beneficial effects of pollen on horse's performance. Only little research has been done to evaluate the efficacy of bee pollen supplementation in horses [23]. The aim of this study was to determine the digestibility of macroelements from different horse feed rations.…”
Section: Introductionmentioning
confidence: 99%